Manajemen Nyeri Berbasis Digital pada Pasien dengan Penyakit Kronis - Anak Agung Ayu Emi Primayanthi; Dewi Gayatri; La Ode Abd Rahman (Journal of Telenursing (JOTING), 2023)
This study aims to find and discuss evidence based on digital-based pain management in patients with chronic diseases. The method used in this research is a systematic review that starts by identifying nursing problems, determining priority problems and research questions, searching for and identifying relevant research, and carrying out data extraction. The research results show four significant scopes of literature searches discussing chronic pain management: telehealth, applications, internet-based therapy, and virtual reality. The conclusion is that digital therapy can help reduce the pain felt by patients. This therapy can be beneficial in the long term because digital therapy is a therapy that is cheap, easy, and can be done anywhere without having to go to a health service. Keywords: Digital Therapy, Pain Management, Pain, Chronic Disease